KCTD15 inhibits the Hedgehog pathway in Medulloblastoma cells by increasing protein levels of the oncosuppressor KCASH2 - Spiombi, Eleonora (Oncogenesis, 2019)
Medulloblastoma (MB) is the most common malignant childhood brain tumor. About 30% of all MBs belong to the I molecular subgroup, characterized by constitutive activation of the Sonic Hedgehog (Hh) pathway. The Hh pathway is involved in several fundamental processes during embryogenesis and in adult life and its deregulation may lead to cerebellar tumorigenesis. Indeed, Hh activity must be maintained via a complex network of activating and repressor signals. One of these repressor signals is KCASH2, belonging to the KCASH family of protein, which acts as negative regulators of the Hedgehog signaling pathway during cerebellar development and differentiation. KCASH2 leads HDAC1 to degradation, allowing hyperacetylation and inhibition of transcriptional activity of Gli1, the main effector of the Hh pathway. In turn, the KCASH2 loss leads to persistent Hh activity and eventually tumorigenesis. In order to better characterize the physiologic role and modulation mechanisms of KCASH2, we have searched through a proteomic approach for new KCASH2 interactors, identifying Potassium Channel Tetramerization Domain Containing 15 (KCTD15). KCTD15 is able to directly interact with KCASH2, through its BTB/POZ domain. This interaction leads to increase KCASH2 stability which implies a reduction of the Hh pathway activity and a reduction of Hh-dependent MB cells proliferation. Here we report the identification of KCTD15 as a novel player in the complex network of regulatory proteins, which modulate Hh pathway, this could be a promising new target for therapeutic approach against MB.